Enhancing STEM education through peeragogy: Exploring the impact of demographics factor - Arsad, Nur Nadia Binti Md; Mei Heong, Yee (Jurnal Pendidikan Teknologi Kejuruan, 2024)
Despite the growing recognition of the peeragogy learning approach, which emphasizes students' active participation and responsibility in their learning, there is still a gap in understanding how demographic factors influence its effectiveness in Science, Technology, Engineering and Mathematics (STEM) education. While pedagogy aims to harness the individual potential to promote independence, collaboration, and deep understanding, few studies have been conducted on how different demographic factors impact the success of this approach. This study aims to identify the trends in the peeragogy learning approach among students for STEM subjects in the Upper Secondary Vocational Program (PVMA) stream based on demographic factors such as gender, STEM subjects, and socioeconomic status (SES). The design of this study is survey research that employs a quantitative approach, and a modified set of questionnaires derived from past studies was used as the research instrument. A total of 158 students enrolled in STEM subjects under the PVMA stream at secondary schools were randomly selected as the study samples. The results indicate that most students in STEM subjects under the PVMA stream prefer a goal-oriented peeragogy learning approach, a consistent trend across both genders. Socioeconomic status also plays a role, with students from varying household income levels generally preferring the self-directed peeragogy learning approach. Different STEM subjects and SES affect PVMA students' choice of peeragogy learning approaches. In conclusion, educational institutions can improve the effectiveness of peeragogy in STEM education for PVMA students by promoting equitable learning opportunities for different SES and developing peeragogy strategies based on different STEM subjects.